(untitled) - Prof. Dr. Monika Eigmüller; Jun.-Prof. Dr. Vincent Gengnagel; Prof. Dr. Klarissa Lueg (Culture, Practice & Europeanization, 2018)
Culture, Practice and Europeanization (CPE) is an open access peer reviewed platform for publishing research-based articles predominantly dealing with research into the multiplicity of social processes, interactions, and policies relating to Europeanization and international encounters in Europe. Perspectives may be interdisciplinary. Empirical, theoretical and conceptual texts of significant originality will be considered for publication. CPE publishes foremost full-length original articles, but will also consider original reviews, conference speeches, and notes in order to inform the research community of most recent developments. CPE welcomes contributions that seek to enhance understanding of social processes relating to internationalization and further trans-national activities and processes in Europe.